An Analysis of Home Environment Quality with Acute of URI (Upper Respiratory Tract Infection) Incident on Toddler Ages in Mayor Umar Damanik Health Center, 2018 - Ahda, Rita (Proceeding - Sari Mutiara Indonesia International Conference on Health, 2018)
According to Riskesdas data in 2013, the prevalence of URI (Upper Respiratory Tract Infection) in Indonesia was 25.0% and the period prevalence of URI in North Sumatra was 19.9%. Data from the Tanjung Balai Health Office reported that 902 people were suffering from URI in 2016. Based on the monthly report of P2 URI, most found in the Major Umar Damanik Health Center, namely 1,404 cases and 518 cases of URI found in infants. Important factors that can increase the occurrence of URI are the physical condition of the house (natural lighting, ventilation area, humidity in the house, air pollution in the house, and occupancy density). The results of Riskesdas in 2013 stated that according to occupancy density, there were 13.4% of houses with a residential density of more than or equal to 8m2 per person (solid). In the Major Umar Damanik Health Center, Tanjung Balai City, February-April 2018, the incidence of URI in infants was 518 cases (43.16%). So it is important to study as an effort to analyze the quality of home sanitation with the incidence of URI in infants in the working area of ​​the Major Umar Damanik Health Center in Tanjung Balai City in 2018. The study was designed using a cross-sectional approach in 69 respondents. There is a relationship between occupancy density, ventilation area, air pollution, humidity, temperature, natural lighting, with the incidence of URI in infants in the Puskesmas Mayor Umar Damanik working area of ​​Tanjung Balai City in 2018. Air pollution in the home is the most dominant factor affecting the incidence of URI in infants in the work area of ​​the Public Health Center of Major Umar Damanik, Tanjung Balai City in 2018. Its recommended that the community improve their knowledge of the requirements of the home environment according to Permenkes RI No. 1077 / MENKES / PER / V / 2011 and apply it